Patterns, Types, and Outcomes of Head Injury in Aseer Region, Kingdom of Saudi Arabia. (7th March 2019) - Alnaami, Ibrahim; Alshehri, Shbeli; Alghamdi, Saeed; Ogran, Meshal; Qasem, Asim; Medawi, Abdulrahman; Medawi, Abdulmajeed; Alshahrani, Saud; Sarhan, Leen
Abstract : Background . Head injuries contribute to almost 50% of all injuries. Head injuries are still one of the major causes of loss of life and loss of function among young adults. Nowadays, head injury has become a major community problem. Recently, head injury has become one of the biggest issues of almost more than 57 million people in the whole world living with the neurological problem raised by TBI, in which 10 million people require hospital base care. Objectives . To determine the epidemiological aspects of patients with head injury (HI) in Aseer Central Hospital (ACH). Materials and Methods . This is a retrospective cross-sectional study. Data were gathered from patients' files and the registrar's database of ACH. The study duration was January 2015–December 2017. All patients with head injury admitted to ACH during the study duration were included in the study. SPSS software was used for analysis. Descriptive statistics were obtained (mean SD frequencies, percentages). Statistical tests, t test, and chi-squared test were applied to measure the significant difference among the variables. P-value less than 0.05 was considered as a significant difference. Results . There were 353 patients with head injury, and the mean ± SD of age was 27.01 ± 13.9. Motor vehicle accidents (MVA) accounted for (89.3%) of head injury. A total of 87.3% of the patients were male while 12.7% were female. Conclusion . In this study, we observed that MVA is the leading cause of brain/head injuries in the KSA, despite the implementations of new speed rules. However, with new regulations of forbidding cell phone use while driving and forcing the seat belt regulations, a major impact on these numbers is expected in the future. Thus, a future study is recommended to assess these expectations.